The problem of ensuring respect for economic human rights in Eastern Europe - V. Shcherbanyuk, Oksana (2020)
Observance of economic rights is the basis of stable economic development of the country. The state is obliged to create appropriate conditions for self-realization. Each state must properly evaluate the work of a person and guarantee decent living conditions. The purpose of the scientific article is to establish the level of economic human rights in Eastern Europe, the factors influencing the implementation of economic human rights, to establish a causal link between economic development and the level of economic human rights in certain countries, to introduce compliance issues, to insert the issue of observance of these rights and development of ways to improve the conditions of observance of economic human rights.